West Bank and Gaza - Municipal Finance and Service Provision - World Bank (World Bank, 2012)
The main general objective of this study is to promote a deeper understanding of municipal finance in the West Bank and Gaza, including identification of the key issues that local governments currently face. The paper discusses the policy implications associated with its main findings as potential policy options for future decision making on local government reforms. As such, this study aims at facilitating the process for a future policy dialogue between the World Bank and the Palestinian Authority (PA) or Ministry of Local Government (MoLG). Furthermore, it is expected that the identification of the main issues, together with their policy implications, may assist the PA or MoLG in the selection of the key areas that could potentially benefit from the World Bank's technical assistance. In particular, this study attempts to: (i) clarify the actual role that municipalities play in the provision of local services; (ii) evaluate the current assignment of municipal revenue sources and determine their adequacy to cover current expenditure functions, including an analysis of whether there are unfunded mandates, and if so, identify the main contributing factors; and (iii) determine the balance between expenditures and revenues aiming primarily to assess whether the current revenue sources cover the estimated costs of the municipal services that are being provided, and draw the corresponding conclusions on the current municipal fiscal situation. Furthermore, this Economic and Sector Work (ESW) highlights the nature and magnitude of current fiscal imbalances across municipalities in the West Bank and Gaza.